Case of fulminant type 1 diabetes induced by the anti‐programmed death‐ligand 1 antibody, avelumab. Issue 5 (19th March 2019) - Shibayama, Yui; Kameda, Hiraku; Ota, Shoichiro; Tsuchida, Kazuhisa; Cho, Kyu Yong; Nakamura, Akinobu; Miyoshi, Hideaki; Atsumi, Tatsuya
Abstract: With the expansive use of immune checkpoint inhibitors, the frequency of immune‐related adverse events, including autoimmune type 1 diabetes, has been exponentially increased. The anti‐programmed death‐ligand 1 antibody, avelumab, has recently been approved for metastatic Merkel cell carcinoma therapy. Here, we report a patient that developed fulminant type 1 diabetes during avelumab treatment. An 81‐year‐old woman with no history of diabetes received avelumab for metastatic Merkel cell carcinoma. Elevated plasma glucose level (483 mg/dL), hemoglobin A1c level (7.5%) and ketosis were observed after 10 courses of avelumab without any symptoms related to hyperglycemia. As the laboratory tests showed insulin depletion, we diagnosed her with fulminant type 1 diabetes induced by avelumab. This is the first reported case of avelumab‐induced type 1 diabetes, illustrating the necessity for close monitoring of glycemic control during avelumab therapy, as well as other immune checkpoint inhibitors. Abstract : This table shows laboratory findings at admission. The laboratory tests showed insulin depletion, we diagnosed the patient with fulminant type 1 diabetes induced by avelumab.